2011
DOI: 10.1002/meet.2011.14504801097
|View full text |Cite
|
Sign up to set email alerts
|

Changes in users' knowledge structures before and after Web search on a topic: Analysis using the concept map

Abstract: In this study, we investigate the changes in users' mental representations of a topic during their exploratory search on the Web. We use concept maps to compare the users' knowledge before and after a search. Participants are required to gather information on the Web as preparation for a regular feature of a magazine on environment and trip topics. They are divided into two scenario groups: divergent and convergent. The divergent scenario requires the gathering of Web pages for an entire series of articles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…A comparative analysis of concept maps between pre-search and post-search maps indicated that users significantly changed their knowledge structures for a topic through an exploratory search. Saito et al [9,10] also confirmed the effects of scenarios on their search activities and knowledge structures. In their experiment, participants were required to gather information on the Web in preparation for a regular magazine feature.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…A comparative analysis of concept maps between pre-search and post-search maps indicated that users significantly changed their knowledge structures for a topic through an exploratory search. Saito et al [9,10] also confirmed the effects of scenarios on their search activities and knowledge structures. In their experiment, participants were required to gather information on the Web in preparation for a regular magazine feature.…”
Section: Introductionsupporting
confidence: 73%
“…These are based on the results of previous studies [3,10,9] • Hypothesis 1: A participant conducting the search condition task browses various web pages and acquires new information; thus, the concept maps drawn by the participants in the search condition task would change dynamically between pre-and post-tasks. Therefore, the number of lost and new nodes in the search condition task would be greater than that of lost and new nodes in the filler condition task.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in this genre, like Saito and colleagues [46] have analysed how participants’ conceptual structures changed when they searched documents for writing magazine articles on certain topics. The participants were asked to draw a conceptual map on the topic of search before and after a 15 min search.…”
Section: Types Of Research On Searching As Learningmentioning
confidence: 99%